Cross-Cutting Themes in Advanced Economies with Emerging Market Banking Links. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The most recent decade has seen a growing presence of banks headquartered in advanced economies (AEs) expanding into emerging markets (EMs). These expansions have brought some benefits to both home and host countries, but the global financial crisis has also unmasked significant vulnerabilities inherent in such relationships. In keeping with past cross-cutting themes papers, this paper focuses on the experiences of four medium-sized ?home countries,? each with significant retail banking links to EMs-Austria, Belgium, the Netherlands, and Spain. These countries were chosen because of their banks' diverse approaches to EM expansion (including the centralization of their funding models) and equally diverse crisis outcomes (fears over Eastern European exposures resulted in extraordinary policy efforts to maintain bank lending), providing fertile ground for analysis and for drawing lessons in the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet